Ghaddhul Bashar dalam Perspektif Hadis - Saputri, Farista Intan; Muhajirin, Muhajirin; Nur, Sulaiman Mohammad (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2023)
The wild gaze of the opposite sex can be the first cause of adultery. Such gaze will lead to fantasies and forbidden desires in the mind and heart. This is what then encourages a person to step over things that are prohibited in religion. Nowadays keeping the view of the forbidden is a difficult matter, moreover our society has been filled with media provoking lust and lust almost everywhere. Related to this in the hadith of the Prophet SAW said that it is not allowed to continue the first view with the next view. The method used is a text study (library research), with the main source of the hadith book Jami' at Tirmidzi. Ghaddhul bashar means to keep the eyes from looking at the aurat of the opposite sex that is not a mahram. The interpretation of this Hadīth is to limit looking at the aurat of the opposite sex by not observing or not paying attention with interest so as to generate desires and fantasies of sinning, because in the Arab tradition a look can be interpreted as an invitation. Hence, it is not permissible to follow up the first glance with another one.